Recent Advances in Tools for Early Identification of Patients with Potential Palliative Care Needs - Chunwei LI, Renli DENG, Cui SU, Bisang ZHUANG (Zhongguo quanke yixue, 2022)
Early recognition of patients who may gain benefits from palliative care will help medical service providers to provide such patients with targeted, patient-centered care, therebyreducing the provision of meaningless overtreatment, and improving negative emotional distress and quality of life of patients as well as the quality of life of patients' families. Many tools developed by foreign scholars for early identifying patients with potential palliative care needs, are mostly consisted of predictors of death risk and early warning signs of deterioration. In particular, some of them have been iteratively updated during the process of global application and verification, and could recognize those who could benefit from palliative care, although their applicability and accuracy levels need to be improved further. In contrast, in China, related research is scarce, and the development and application of such tools are still in the preliminary stage. In accordance with the classification of applicable diseases and people, we classified the tools for early identifyingpatients with potential palliative care needs, reviewed their main contents, characteristics and applications, thenmade a comparative analysis of the common tools in terms of basic essentials and application, with a view to providing a reference for the development and localization of such tools, and for accurateassessment and provision of potential palliative care for those who can benefit from such care.